The impact of corporate culture on ethical perception and unethical behavior - Kratz, Anna (2024)
Unethical decisions have been a part of organizations ever since they were formed. Still, ethical misconduct is often overlooked, not only because individuals are still hesitant to voice ethical concerns, but also because of their susceptibility to external influences in their environment. Corporate culture may reduce unethical behavior in organizations, through its role as a driver of ethical decision-making and its potential influence on whistleblowing intentions. In this thesis, existing research is reviewed, and corporate culture is explored as a factor of influence for unethical behavior and perception, as well as potential dependencies between the two components of the ethical decision-making process. Through an experimental study with a sample of 163 participants, the effects of two contrasting hypothetical corporate cultures were investigated through ethical vignettes. The results, while explicitly hypothetical for behavior, demonstrated a significant influence of corporate culture on unethical behavior, even when controlling for social desirability and ethical orientation. Regarding the influence of the latter, corporate culture seemed to play an even more important role when the ethical orientation of participants was low. In contrast, corporate culture had no significant effect on ethical perception. This thesis sheds light on new potential factors of influence impacting the effect of corporate culture on perception and unethical behavior, contributing to the existing literature of the influences of corporate culture and providing new research approaches.